2017
DOI: 10.4269/ajtmh.16-0781
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Real-Time Polymerase Chain Reaction Assays for the Detection of 20 Gastrointestinal Parasites in Clinical Samples from Senegal

Abstract: Gastrointestinal parasite infections represent one of the biggest public health problems in the world. Therefore, appropriate innovative tools are needed for assessing interventions to control these infections. This study aims to compare the performance of real-time polymerase chain reaction (PCR) assays to microscopic examination for detection of intestinal parasites. A direct microscopic examination and stool concentration was performed on 98 stool samples from patients attending Senegalese hospitals. Negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The primers and probes detailed in the paper of Sow et al [30] were used to assay the twenty gastrointestinal eukaryotic pathogens on the CFX96TM and CFX384TM real-time PCR detection systems (BIO-RAD, Life Science, Marnes-la-coquette, France). The amplification reaction included 10 µL of master mix (Roche diagnostics GmbH, Mannheim, Germany), 0.5 µL of each primer, 0.5 µL of probe, 3 µL of distilled water, 0.5 µL of uracil-DNA glycosylase (UDG), and 5 µL of DNA in a total volume of 20 µL.…”
Section: Real-time Pcr Assaysmentioning
confidence: 99%
“…The primers and probes detailed in the paper of Sow et al [30] were used to assay the twenty gastrointestinal eukaryotic pathogens on the CFX96TM and CFX384TM real-time PCR detection systems (BIO-RAD, Life Science, Marnes-la-coquette, France). The amplification reaction included 10 µL of master mix (Roche diagnostics GmbH, Mannheim, Germany), 0.5 µL of each primer, 0.5 µL of probe, 3 µL of distilled water, 0.5 µL of uracil-DNA glycosylase (UDG), and 5 µL of DNA in a total volume of 20 µL.…”
Section: Real-time Pcr Assaysmentioning
confidence: 99%
“…Frequent efforts of the scientific community have been made to improve the diagnostic accuracy of tests for different enteroparasites of medical interest, including S. stercoralis [10,23,24]. To understand the need for these new diagnostic or epidemiological study tools, a recent comparative study with 98 samples concluded that there were discrepancies between molecular tests (real-time PCR) and microscopic methods for the diagnosis of 20 enteroparasites [25]. As previously mentioned, the method for the detection of immunocomplexes using the anti-Strongyloides sp.…”
Section: Discussionmentioning
confidence: 99%
“…and DNeasy® Blood & Tissue according to the manufacturer's instructions. The DNA extraction quality was assessed by RT-PCR targeting internal control TISS phage that was added to each extraction [19].…”
Section: Dna Extractionmentioning
confidence: 99%